INVESTIGATIONS OF PARAMETERS OF THE ROLLING-AND-SEPARATION PROCESS AT PRODUCTION OF REINFORCING PROFILES ON THE MILL 320 OF RUP "BMZ - S. M. Zhuchkov; V. A. Matochkin; D. N. Andrianov; O. M. Kirilenko; N. I. Anelkin; P. V. Tokmakov; D. S. Chernenko (Литьë и металлургия)
The investigations of energy-power, temperature-high-speed and deformational parameters of rolling of reinforcing profile No 10 using the process of MPR with division into four strings at production of the reinforce rolled metal on the mill 320 PUKP ''BMZ” are carried out.